Children mortality in Pediatric Intensive Care Unit (PICU): An Overview - Tuti Seniwati; Asma Danisa Hasmuddin; Titi Iswanti Afelya (Jurnal Kesehatan Pasak Bumi Kalimantan, 2022)
Introduction: Pediatric Intensive Care Unit (PICU), is unit of care spesifically for children who have critical medical condition. Critical condition experienced by children treated at PICU are inseparable from emergencies and can be at risk of death. Even though the child mortality rate has decreased every year, the incidence of mortality in the PICU is still a large contributor to the death of children at this time. Objective: To identify characteristics of children mortality in the PICU hospital unit Dr. Wahidin Sudirohusodo Makassar. Method: This study was an analytic survey using a cross-sectional design with purposive sampling. Results: The study of 53 children medical records showed that the average respondent aged 59 months (SD 69.29) experienced death, length of stay of respondents who experienced death was 7.94 days (SD 9,69), the neurological status of patients at the beginning of admission shows the value of 11.43 (SD 4,496). Patients with a diagnosis of sepsis showed the highest mortality in this study. Conclusion: Respondents with infant categories, mild neurological status at the admission of PICU, used mechanical ventilators as oxygen devices, have the highest frequency of mortality in PICU. Hence, this study suggested to the other researcher to examine the variables that relate to child mortality in PICU for revealed as a whole.